The impact of foreign direct investment and government expenditure on economic growth: Empirical evidence from Indonesian economy - Ratna Mutia; Khairul Aswadi; Martahadi Mardhani; Amiruddin Hasan; Amrusi Amrusi (Jurnal Sains Sosio Humaniora, 2021)
This paper examines the impact of economic growth through foreign direct investment and government expenditure for 2000-2020 on the Indonesian economy. We have applied an ordinary least squares regression (OLS) approach to estimate these parameters. Our findings show that government expenditure and foreign direct investment (FDI) positively and significantly impact economic growth. Further research using disaggregated data is needed to determine the more profound impact on economic growth.